Mechanical and wear performance of Al/SiC surface composite prepared through friction stir processing - Ravi Butola; Lakshay Tyagi; Ranganath M Singari; Qasim Murtaza; Harish Kumar; Dhiraj Nayak (Materials Research Express, 2021)
In the present research work, AA7075 composite reinforced with silicon carbide particles has been fabricated using Friction stir processing (FSP). The silicon carbide particles having a size of 40 μ m were placed in grooves of length 160 mm, width 2 mm, depth 3.5 mm, that were generated on the AA7075 plate. The square pin tool is utilized for fabricating the composite at two different rotational speed i.e. 700 and 1000 rpm. Effect of processing, particle addition and tool rotational speed is analyzed on mechanical and wear properties of the material. On friction stir processing the microhardness value and elongation of the material increased. Reinforcement addition contributed to decrease in ductility and tensile strength while on the contrary microhardness and wear resistance of the material improved. Tool rotational speed showed a direct relation with the tested mechanical and wear properties. Adhesive wear was the prominent wear mechanism and Fe layer formation was observed on the worn surface, contributing to increased wear resistance. These fabricated composites can find vast application in industries like automotive, defence and aerospace.